1973
DOI: 10.2527/jas1973.372459x
|View full text |Cite
|
Sign up to set email alerts
|

Postweaning Performance of Pigs from Gilts Fed Diets High and Low in Protein during Gestation and Lactation

Abstract: T WO experiments involving 296 pigs from gilts fed diets containing low (2%) or adequate (17%) protein during gestation followed by 5% or 17% during lactation were conducted to determine the effect of maternal dietary protein level on performance of the progeny. Blood hematocrit, hemoglobin and plasma protein levels were not affected by the dietary treatments imposed on the dam during gestation. In the first experiment, pigs reared by dams fed adequate protein diets during gestation and lactation retained less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The findings in the 1970s that decreased protein levels had little effect on litter size compared with previously recommended protein levels was also important. In fact, some studies showed that sows could be fed extremely low protein levels during gestation without affecting litter size or pig weights, but it had a dramatic negative effect on milk production during the subsequent lactation period and on return to estrus (Pond et al, 1963;DeGeeter et al, 1972DeGeeter et al, , 1973.…”
Section: Feeding Programs For Gestating and Lactating Sowsmentioning
confidence: 99%
“…The findings in the 1970s that decreased protein levels had little effect on litter size compared with previously recommended protein levels was also important. In fact, some studies showed that sows could be fed extremely low protein levels during gestation without affecting litter size or pig weights, but it had a dramatic negative effect on milk production during the subsequent lactation period and on return to estrus (Pond et al, 1963;DeGeeter et al, 1972DeGeeter et al, , 1973.…”
Section: Feeding Programs For Gestating and Lactating Sowsmentioning
confidence: 99%